Promoting Students Autonomy through Quizlet - Dicky Abdillah; Thohiriyah Thohiriyah (Universitas Muhammadiyah Semarang, 2018)
21st century era offers the ease of internet access and information accessibility which then demands people to be autonomous in all aspects, not limited to the English teaching-learning context. Quizlet is a digital app which considered as an influential and authentic tool to promote students autonomy as it is multimodal. This paper is aimed to review the Quizlets multimodality which considered promoting students autonomy in learning English. Quizlet provides auditory and visual inputs through its features to build up students autonomy.